Interaction of N -acetylcysteine with DPPC liposomes at different pH: a physicochemical study - Arias, Juan Marcelo (2020)
The N-acetylcysteine (NAC) is a commonly used mucolytic and antioxidant agent. The knowledgeof interactions of the NAC with cell membranes is important to understand its mechanism ofpharmacological action at the molecular level. To gain a deeper insight into analyzing N-acetylcysteineinteractions with multilamellar liposomes of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) inhydrated states at different pH, we performed experimental studies by differential scanning calorimetry(DSC), Fourier transform infrared spectroscopy (FTIR), and Raman spectroscopy. The behavior of theasymmetric stretching band of the PO2 group was studied by FTIR following the changes that occur inthe shape of this band in the pretransition and transition stages from the gel state to the crystallineliquid state. The values of the pretransition temperature (Tp) for different molar ratios of the complex atthe two pH values studied were coincident between the measurements by FTIR and DSC, with theresults reaffirming the importance of the PO2 group as a sensor not only in the state of hydration butalso in the formation of new intermolecular bonds, which lead to the formation of different domains.The vibrational behavior of the groups of the polar head of the lipid revealed the role of the lipid as anoxidant on the thiol site of the NAC. The results of these studies provide information on membraneintegrity and its physicochemical properties. In this aspect, this work has novelty and practicality inpharmacology and analytical chemistry